Bio-management of Cucumber Wilt Complex Caused by Root-knot Nematode, Meloidogyne incognita and Fusarium oxysporum f. sp. cucumerinum in Polyhouse under Protected Cultivation - Jaydeep Patil; S.R. Goel; Saroj Yadav (Journal of Pure and Applied Microbiology, 2017)
A polyhouse study was conducted to determine the potential of biocontrol agents viz. Trichoderma viride, Pseudomonas fluorescence, Purpureocillium lilacinum (Paecilomyces lilacinus) @ 0.3 and 0.5 g/kg soil and liquid formulation of bioagents, (T. viride + P. fluorescence + P. lilacinus) @ 0.5 and 1 ml/ kg soil, against root-knot nematode, Meloidogyne incognita and Fusarium oxysporum f. sp. cucumerinum disease complex on cucumber. Three main treatments, viz., nematode alone, fungus alone and both inoculated simultaneously were taken. Chemical checks with Bavistin @ 2 g/ l water and carbofuran @ 0.1 mg/ kg soil as well as untreated check were also maintained. Fungus was grown on sand maize meal medium. Soil was autoclaved and infested with root-knot nematode (1000 J2/ kg soil) and fungus (50 g/ kg soil). The bio-agents were mixed with the potted soil treatment wise. A waiting period of three days was given for multiplication of bioagents on the organic matter before sowing. All the treatments significantly improved the plant growth parameter, viz., shoot length (SL), root length (RL), fresh shoot weight (FSW), fresh root weight (FRW), dry shoot weight (DSW) and dry root weight (DRW) as compared to untreated check. However, maximum improvement in plant growth parameter was recorded in case of carbofuran @ 0.1 mg /kg soil followed by higher dose liquid formulation of bioagents. Bavistin was least effective among all the treatments against root-knot nematode, Meloidogyne incognita and Fusarium oxysporum f. sp. cucumerinum disease complex.